Immune response to Bifidobacterium bifidum strains support Treg/Th17 plasticity. - Patricia López (Public Library of Science (PLoS), 2011)
In this work we analyzed the immune activation properties of different Bifidobacterium strains in order to establish their ability as inductors of specific effector (Th) or regulatory (Treg) responses. First, we determined the cytokine pattern induced by 21 Bifidobacterium strains in peripheral blood mononuclear cells (PBMCs). Results showed that four Bifidobacterium bifidum strains showed the highest production of IL-17 as well as a poor secretion of IFNγ and TNFα, suggesting a Th17 profile whereas other Bifidobacterium strains exhibited a Th1-suggestive profile. Given the key role of Th17 subsets in mucosal defence, strains suggestive of Th17 responses and the putative Th1 Bifidobacterium breve BM12/11 were selected to stimulate dendritic cells (DC) to further determine their capability to induce the differentiation of naïve CD4(+) lymphocytes toward different Th or Treg cells. All selected strains were able to induce phenotypic DC maturation, but showed differences in cytokine stimulation, DC treated with the putative Th17 strains displaying high IL-1β/IL-12 and low IL-12/IL-10 index, whereas BM12/11-DC exhibited the highest IL-12/IL-10 ratio. Differentiation of naïve lymphocytes confirmed Th1 polarization by BM12/11. Unexpectedly, any B. bifidum strain showed significant capability for Th17 generation, and they were able to generate functional Treg, thus suggesting differences between in vivo and vitro responses. In fact, activation of memory lymphocytes present in PBMCS with these bacteria, point out the presence in vivo of specific Th17 cells, supporting the plasticity of Treg/Th17 populations and the key role of commensal bacteria in mucosal tolerance and T cell reprogramming when needed.